Legal protection for women victims of sexual violence during the covid 19 pandemic in Surakarta City - Raden Roro Astuti Retno Lestari; Khudzaifah Dimyati; Kelik Wardiono (Trigin Publisher, 2023)
Protection of sexual violence is a human right guaranteed by the constitution. Non doctrinal research with qualitative descriptive. The aim is to find out and analyze the legal protection of women victims of sexual violence during the Covid 19 pandemic in the city of Surakarta according to statutory regulations. The results of the 2020 study totaled 40 cases with 26 cases of domestic violence, 6 cases of rape, 5 cases of sexual abuse, and 3 cases of dating violence. Legal protection for victims of rape sexual violence in Surakarta City began with the stages of investigation, prosecution and trial. However, the right to a new identity, reimbursement of transportation costs as needed, determining the form of protection and security support was almost never given. In addition, the government's policy of limiting the conditions of the Covid 19 pandemic has slowed down the handling of victim protection. The investigative phase is carried out face to face with health protocols, while the prosecution and examination courts and trials are conducted online by maintaining the confidentiality of the victim's identity but causing limited interaction between victims, prosecutors and judges. The right to legal protection for victims of female sexual violence during the Covid 19 pandemic has not been fully fulfilled in Surakarta City.